-5(7n-4)+3=

Simple and best practice solution for -5(7n-4)+3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(7n-4)+3= equation:


Simplifying
-5(7n + -4) + 3 = 0

Reorder the terms:
-5(-4 + 7n) + 3 = 0
(-4 * -5 + 7n * -5) + 3 = 0
(20 + -35n) + 3 = 0

Reorder the terms:
20 + 3 + -35n = 0

Combine like terms: 20 + 3 = 23
23 + -35n = 0

Solving
23 + -35n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-23' to each side of the equation.
23 + -23 + -35n = 0 + -23

Combine like terms: 23 + -23 = 0
0 + -35n = 0 + -23
-35n = 0 + -23

Combine like terms: 0 + -23 = -23
-35n = -23

Divide each side by '-35'.
n = 0.6571428571

Simplifying
n = 0.6571428571

See similar equations:

| 2y-14=4y+4 | | P=2(26)+2(91) | | 5y+6y-81=7y+102+65 | | 3t^4=8t | | x+x+125000=550000000 | | 12x+8y-12=0 | | 4*x-9/2+12=0 | | 51x^2-5x-4= | | x+x+4=238 | | -(6y+5)-(-5y-7)=-5 | | 14-2x+39x-18x=256-60x-657x | | 13-42/7 | | 7+3p-4=9p+10-5p | | -x/3+58= | | -3b=-12 | | 2b+3(b-2)=4 | | -14n+4=-13n-17 | | -8w^2-8w+19=0 | | 12y=11(y+1) | | 4n+10n=28 | | -7.7x=15.4 | | 7-(5x-12)=1/3(4x+60) | | 16-11x+12=-15x | | -57+23+x= | | r-15=-13 | | t(4+1)=0 | | 1.6q-3.3-2.2q=-1.6q-4.7 | | 2x+0.8-3.5=x | | 37x-625=0 | | 36= | | 25s^2+90sp+81p^2= | | 1/w-1=-8-5/w-2 |

Equations solver categories